Idiomatic variants and synonymous idioms in English - Giang, Dang Nguyen (VNU Journal of Foreign Studies, 2009)
Abstract. This article is about the following issues: - Defining the concepts of “idiomatic variants” and “synonymous idioms” - Criteria for the distinction between idiomatic variants and synonymous idioms - Forms and signs of idiomatic variants and synonymous idioms